(Plenary) Printed Electrochemical Instruments for Biosensors. (20th July 2015) - Beni, Valerio; Nilsson, David; Arven, Patrik; Norberg, Petronella; Gustafsson, Göran; Turner, Anthony Peter Francis
Abstract : Mobile diagnostics for healthcare, food safety and environmental monitoring, demand a new generation of inexpensive sensing systems suitable for production in high volume. Herein we report on the development of a new disposable electrochemical instrument exploiting the latest advances in printed electronics and printed biosensors. The current system is manufactured under ambient conditions with all interconnections printed; electrochemical measurements and data elaboration are realized by the integration onto the platform of two chips: a MICROCHIP-PIC24F16KA101 and a Texas Instrument's LMP91000. A PEDOT.PSS vertical electrochromic display (VECD) is also incorporated into the system to visualize the data. A printed Enfucell 3V manganese dioxide battery was used to deliver the required power. Finally, in order to demonstrate the utility of the system, screen-printed sensors for the detection of glucose were added and the performance of the overall system was evaluated.